DIGITALISATION OF TEACHING AND LEARNING METHODS IN STATISTICS - DANIELA-EMANUELA DĂNĂCICĂ (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
The aim of this article is to analyse the digitalisation of teaching and learning methods in statistics. A dataset of 49 open-access papers published in WoS journals between 2010 and 2025 was analysed. The results indicate that the use of digital tools such as SPSS, R, Python, EViews, Stata, e-learning platforms, gamification and virtual/augmented reality contributes to improving academic performance, student motivation and engagement, while also facilitating the acquisition of advanced digital and analytical skills required by today's labour market.